2011
DOI: 10.1038/cddis.2011.8
|View full text |Cite
|
Sign up to set email alerts
|

Individual caspase-10 isoforms play distinct and opposing roles in the initiation of death receptor-mediated tumour cell apoptosis

Abstract: The cysteine protease caspase-8 is an essential executioner of the death receptor (DR) apoptotic pathway. The physiological function of its homologue caspase-10 remains poorly understood, and the ability of caspase-10 to substitute for caspase-8 in the DR apoptotic pathway is still controversial. Here, we analysed the particular contribution of caspase-10 isoforms to DR-mediated apoptosis in neuroblastoma (NB) cells characterised by their resistance to DR signalling. Silencing of caspase-8 in tumour necrosis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 37 publications
(55 reference statements)
3
29
0
Order By: Relevance
“…Since cell death in neuroblastoma cells through TRAIL-R2 is thought to be mediated chiefly through caspases-8, 22 caspase-8 basal expression was examined by immunoblotting. In our panel of seventeen cell lines, basal expression of the p54 and p55 isoforms of caspase-8 was observed only in CHLA-79, LA-N-2, and LA-N-6 cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since cell death in neuroblastoma cells through TRAIL-R2 is thought to be mediated chiefly through caspases-8, 22 caspase-8 basal expression was examined by immunoblotting. In our panel of seventeen cell lines, basal expression of the p54 and p55 isoforms of caspase-8 was observed only in CHLA-79, LA-N-2, and LA-N-6 cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…21 In neuroblastoma cells, previous findings indicate that caspase-8 may be the chief arbitrator of cell death downstream of cross-linking of soluble TRAIL, when anti-Flag antibody was used to cross-link recombinant Flag-TRAIL. 22 In a large panel of neuroblastoma cell lines that contained a subset expressing basal caspase-8 and caspase-10, caspase-10 expression paralleled that of caspase-8 but was several-fold lower, and incomplete knock-down of caspase-8 in TRAIL-sensitive neuroblastoma cell lines rendered the cells resistant to apoptosis induced by cross-linked TRAIL, regardless of their endogenous expression of caspase-10. This suggested that the relatively low expression of endogenous caspase-10 was not sufficient to initiate apoptosis, even in the presence of a low level of caspase-8 expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with other studies reporting an inhibitory function of the procaspase-8 and -10 prodomains as well as short isoforms of both procaspases. 21,44,45 On the contrary, it has been reported that the procaspase-8 prodomain induces apoptosis upon overexpression. 46 These different findings may be cell type specific or dependent on the level of procaspase-8 prodomain overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…In type I cells, the procaspase-8 and procaspase-10 form homodimers. This induces a conformational change that exposes their proteolytical active sites, resulting in autoactivation and subsequent cleavage of additional procaspase-8 and procaspase-10 molecules leading to activation of suicient caspase-8 to stimulate efector caspase-3 to induce apoptosis [22][23][24]. However, type II cells generate less-active caspase-8 at the DISC.…”
Section: Trail Signalingmentioning
confidence: 99%